Sleep quality and the evolution of the COVID-19 pandemic in five European countries - Samira Jabakhanji; Anthony Lepinteur; Giorgia Menta; Alan T. Piper; Claus Vögele (Freie Universität Berlin, School of Business & Economics, 2022)
The COVID-19 pandemic has led to lifestyle changes across Europe with a likely impact on sleep quality. This investigation considers sleep quality in relation to the evolution of the COVID-19 pandemic in five European countries. Using panel regressions and keeping policy responses to COVID-19 constant, we show that an increase in the four-week average daily COVID-19 deaths/100,000 inhabitants (our proxy for the evolution of the pandemic) significantly reduced sleep quality in France, Germany, Italy, Spain, and Sweden between April 2020 and June 2021. Our results are robust to a battery of sensitivity tests and are larger for women, parents and young adults. Additionally, we show that about half of the reduction in sleep quality caused by the evolution of the pandemic can be attributed to changes in lifestyles, worsened mental health and negative attitudes toward COVID-19 and its management (lower degree of confidence in government, greater fear of being infected). In contrast, changes in one's own infection-status from the SARS-CoV-2 virus or sleep duration are not significant mediators of the relationship between COVID-19-related deaths and sleep quality.
urn:nbn:de:kobv:188-refubium-36454-5
Keywords: I12; I18; J18; 330; COVID-19; Sleep Quality; Mental Health; Public Policy; Coronaphobia